New HSK Tingkat Dasar sebagai Target Kompetensi Pembelajaran Bahasa Mandarin di Sekolah Menengah - Budianto, Pauw (Zenit, 2015)
This research aims to find out the possibility of implementing New HSK basic as the competence target for Mandarin teaching in high school in Indonesia. The methods used in this research is analytical descriptive that used primary and secondary data, with quantitative and qualitative analysis. Results show that the New HSK basic is very possible to be the competence target for Mandarin teaching in high school, and it also will make high school students Mandarin competence will be recognized internationally and able to compete globally.Keywords: New HSK basic, competence target, Mandarin teaching, high school